The Impact of Modernization on Traditional Perahus in Banjarmasin South Kalimantan Indonesia in the Twentieth Century - Susilowati, Endang (Paramita: Historical Studies Journal, 2021)
Abstract: This article studies the impact of modernization on traditional means of transportation in Banjarmasin port, South Kalimantan. Model of à Campo which is generally chosen when traditional sector is set against the modern, i.e. adoption, adaptation, relocation, and withdrawal (exit) is used to analyze the issues in this article. The results of this study show only two options that match with the model, i.e. adaptation and relocation when traditional perahu (Indonesian) faced modern shipping and trade in Banjarmasin port. Adaptation is the right choice, as the perahus will continue to exist. Often perahus do not have any other choice but to relocate their shipping and trading activities to a smaller pier in the hinterland of South Kalimantan. Abstrak: Artikel ini mengkaji dampak modernisasi pada alat transportasi tradisional di pelabuhan Banjarmasin, Kalimantan Selatan. Model à Campo yang umumnya dipilih ketika sektor tradisional berlawanan dengan yang modern, yaitu adopsi, adaptasi, relokasi, dan penarikan (keluar) digunakan untuk menganalisis isu-isu dalam artikel ini. Hasil penelitian menunjukkan hanya dua pilihan yang sesuai dengan model, yaitu adaptasi dan relokasi ketika perahu tradisional (Indonesia) menghadapi pelayaran dan perdagangan modern di pelabuhan Banjarmasin. Adaptasi adalah pilihan yang tepat, karena perahu-perahu akan terus ada. Seringkali perahu-perahu tidak punya pilihan lain selain merelokasi aktivitas pelayaran dan perdagangannya ke dermaga yang lebih kecil di pedalaman Kalimantan Selatan.